Investigation of the Relationship Between Methods of Coping with Stress and Psychological Resilience Levels of Referees - Aksu, Atakan (My University, 2023)
This study aims to examine the relationship between referees' coping strategies for stress and their levels of psychological resilience. The sample group of the study consisted of 212 football referees officiating in the football leagues in Turkey in 2022. The data collection tools used in this study were the Demographic Information Form, the Brief Resilience Scale, and the Coping Response Inventory. Descriptive statistics, t-test, one-way ANOVA, correlation test, and post-hoc (Tamhane's) T2 were used for data analysis. It was observed that there was no statistically significant difference in the scores of the participants on the Brief Resilience Scale and the Coping Response Inventory according to the variables of marital status, gender, and referee classification (p>0.05). However, it was found that there was a statistically significant difference in the scores of the subscales of seeking professional support on the Brief Resilience Scale and the Coping Response Inventory according to the variable of previous experience in playing football, favoring those who had previously played football (p